Riccia junghuhniana, (Ricciaceae, Marchantiophyta) a new record for India from the state of Tamil Nadu - Suresh, N.; Cargill, D. Christine (Phytotaxa, 2024)
Riccia junghuhniana is reported for the first time on the sub-continent of India. A morphological description including images of the gametophyte and micrographs of spores of the Tamil Nadu plants of Riccia junghuhniana are provided to facilitate identification.